Neurocalcin Delta Knockout Impairs Adult Neurogenesis Whereas Half Reduction Is Not Pathological - Upadhyay, Aaradhita; Hosseinibarkooie, Seyyedmohsen; Schneider, Svenja; Kaczmarek, Anna; Torres-Benito, Laura; Mendoza-Ferreira, Natalia; Overhoff, Melina; Rombo, Roman; Grysko, Vanessa; Kye, Min Jeong; Kononenko, Natalia L.; Wirth, Brunhilde (Frontiers in Molecular Neuroscience, 2019)
Neurocalcin delta (NCALD) is a brain-enriched neuronal calcium sensor and its reduction acts protective against spinal muscular atrophy (SMA). However, the physiological function of NCALD and implications of NCALD reduction are still elusive. Here, we analysed the ubiquitous Ncald knockout in homozygous (NcaldKO/KO) and heterozygous (NcaldKO/WT) mice to unravel the physiological role of NCALD in the brain and to study whether 50% NCALD reduction is a safe option for SMA therapy. We found that NcaldKO/KO but not NcaldKO/WT mice exhibit significant changes in the hippocampal morphology, likely due to impaired generation and migration of newborn neurons in the dentate gyrus. To understand the mechanism behind, we studied the NCALD interactome and identified mitogen-activated protein kinase kinase kinase 10 (MAP3K10) as a novel NCALD interacting partner. MAP3K10 is an upstream activating kinase of c-Jun N-terminal kinase (JNK), which regulates adult neurogenesis. Strikingly, the JNK activation was significantly upregulated in the NcaldKO/KO brains. Contrary, neither adult neurogenesis nor JNK activation were altered by heterozygous Ncald deletion. Taken together, our study identifies a novel link between NCALD and adult neurogenesis in the hippocampus, possibly via a MAP3K10-JNK pathway and emphasizes the safety of using NCALD reduction as a therapeutic option for SMA.